Pengembangan Modul Mata Kuliah Bahasa Indonesia Berbasis Case Method Bagi Mahasiswa - Payana, Wita Dwi; Sar, Siswantia; Tahir, Muhammad (Universitas Negeri Padang, 2024)
The development of an Indonesian language module based on the case method is the aim of this research. The type of this research is developmental research involving subject matter experts, design experts, professors, and students. The experiment was conducted involving 2 individual students, 5 small-group students, and 10 limited-group students. The module's quality was obtained in the form of data through questionnaire responses. The findings of this research indicate that: (1) the validation process by the subject matter experts obtained an excellent predicate with a total of 93.25%, (2) the assessment by the design experts received a very good response with a percentage of 91.75%, (3) the limited-group trial achieved an excellent result of 94.99%, (4) the module's effectiveness has an average of 92.00%, which is very good. It can be concluded that the Indonesian language module based on the case method, which has gone through the development process, is suitable for use in academic activities as a learning resource.Keywords: Development, Module, Indonesian Language, Case Method.